2020
DOI: 10.1148/radiol.2020201491
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial Intelligence Augmentation of Radiologist Performance in Distinguishing COVID-19 from Pneumonia of Other Origin at Chest CT

Abstract: AI assistance improved radiologists' performance in distinguishing COVID-19 from pneumonia of other etiology on chest CT. Key Results: An AI model had higher test accuracy (96% vs 85%, p<0.001), sensitivity (95% vs 79%, p<0.001), and specificity (96% vs 88%, p=0.002) than radiologists. In an independent test set, our AI model achieved an accuracy of 87%, sensitivity of 89% and specificity of 86%. With AI assistance, the radiologists achieved a higher average accuracy (90% vs 85%, p<0.001), sensitivity (88% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
386
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(389 citation statements)
references
References 21 publications
0
386
0
3
Order By: Relevance
“…An overall lung involvement score was reached by summing the 5 lobe scores (0-20). Besides, quantitative CT assessment methods and artificial intelligence applications can be successfully applied in the diagnosis of COVID-19 and in the evaluation of disease severity [37,52,53].…”
Section: The Severity Of Pulmonary Involvement On Ctmentioning
confidence: 99%
“…An overall lung involvement score was reached by summing the 5 lobe scores (0-20). Besides, quantitative CT assessment methods and artificial intelligence applications can be successfully applied in the diagnosis of COVID-19 and in the evaluation of disease severity [37,52,53].…”
Section: The Severity Of Pulmonary Involvement On Ctmentioning
confidence: 99%
“…Further, these tools are limited in their ability to differentiate COVID-19 from phenotypically similar diseases. [15][16][17][18] Central to the diagnostic process are ground-glass opacities (GGOs), the radiological finding that indicates the presence of not only COVID-19 but also many similar diseases. 6,[12][13][14] While it is * While we often discuss "diagnosis," the tool here developed can be used for screening and/or complementing other techniques, including radiologists' examination; as such, the results in this work should be considered for a broad range of applications and deployments.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts at making models more transparent have focused on using activation maps but leave ambiguity as to how a diagnosis was assigned and lack the clarity needed for human verification. [15][16][17][18] By focusing on interpretability, our model was also able to refine the previously suspected heterogeneity of GGOs.…”
Section: Review Of Errorsmentioning
confidence: 99%
“…Current studies have demonstrated that arti cial intelligence could distinguish COVID-19 from other pneumonia [11,12], improve radiologists' performance in distinguishing COVID-19 from non-COVID-19 pneumonia on chest CT and provide clinical prognosis with good accuracy that can assist clinicians to timely adjust their clinical management and allocate resources appropriately [13][14][15][16][17][18][19]. However, COVID-19 is caused by SARS-CoV-2 virus, its CT manifestations resemble other types of viruses.…”
mentioning
confidence: 99%